Anaphylaxis in Victoria: presentations to emergency departments, with a focus on drug‐ and antimicrobial‐related cases. Issue 10 (21st March 2022) - Drewett, George P; Encena, Jess; Gregory, Joy; Franklin, Lucinda; Trubiano, Jason A
Abstract: Objective: To investigate the causes, characteristics, and outcomes of anaphylaxis, particularly drug‐related anaphylaxis, in Victoria during the first two years of mandatory notification. Design: Review of all anaphylaxis cases reported by emergency departments to the Victorian Department of Health and Human Services. Setting, participants: People presenting to all public and private hospital emergency departments in Victoria, 1 November 2018 – 31 December 2020. Main outcome measures: Rates of drug‐ and food‐related anaphylaxis, by age group; characteristics of cases of drug‐related anaphylaxis. Results: A total of 4273 anaphylaxis episodes were reported (females: 2292 cases, 54%); the overall anaphylaxis rate was 31.9 episodes per 100 000 person‐years. The most frequently reported causes were foods (2659 cases, 62%); drugs were implicated in 533 cases (12%), insect venoms in 342 (8%), and other causes in 144 (4%). No deaths were recorded. The median age in cases of food‐related anaphylaxis was 17 years (IQR, 6–29 years), and 45 years (IQR, 30–60 years) in cases of drug‐related anaphylaxis. Hospitalisation was required by 1538 patients (36%) and intensive care by 111 (2.6%; 7% of people admitted to hospital). Antimicrobial drugs were implicated in 258 cases of drug‐related anaphylaxis (48%) and non‐steroidal anti‐inflammatory drugs in 85 cases (16%). Penicillin‐class agents were implicated in 143 cases of antimicrobial‐related anaphylaxis (56%), cephalosporins in 80 cases (31%). Conclusion: Our review of notified cases of anaphylaxis in Victoria over two years provides insights into drug‐ and antimicrobial‐related anaphylaxis in non‐hospitalised people presenting to emergency departments.